Comparative intraocular pressure measurements using three different rebound tonometers through in an ex vivo analysis and clinical trials in canine eyes. (5th June 2020) - Shim, Jaeho; Kang, Seonmi; Park, Yoonji; Kim, Sunhyo; Go, Seokmin; Lee, Eunji; Seo, Kangmoon
Abstract: Objective: To evaluate the clinical relevance of intraocular pressure (IOP) measured with three different rebound tonometers in an ex vivo analysis and clinical trials in dogs. Animals and procedures: Ex vivo analysis and clinical trials were performed separately. For the ex vivo analysis, eight enucleated eyes were obtained from four Beagle dogs. IOP values measured with TONOVET ® (TV‐IOP), TONOVET‐Plus ® (TVP‐IOP), and SW‐500 ® (SW‐IOP) were compared with manometric IOPs. For clinical trials, each tonometer was evaluated separately, depending on whether TVP‐IOP was higher or lower than 14 mm Hg. One‐way repeatedmeasures analysis of variance, simple linear regression analysis, and Bland‐Altman plots were used for statistical analyses. Results: In ex vivo analysis, TV‐IOP and TVP‐IOP were not significantly different from manometric IOP. However, SW‐IOP underestimated IOP compared to manometry. Higher discrepancy was observed in TV‐IOP and SW‐IOP with an increase in manometric IOP. In clinical trials, no significant difference was observed between TV‐IOP (9.73 ± 2.92) and TVP‐IOP (11.36 ± 2.23) when TVP‐IOP was lower than 14 mm Hg, but SW‐IOP (8.70 ± 3.03) was significantly lower than TVP‐IOP. TV‐IOP (15.96 ± 6.47) and SW‐IOP (13.09 ± 3.72) were significantly lower than TVP‐IOP (20.08 ± 6.60) when the IOP was higher than 14 mm Hg of TVP‐IOP. Conclusions: This study demonstrates that the TONOVET ® and TONOVET‐Plus ® provide a useful approach for ex vivo analysis. In clinical trials, results of TV‐IOP and SW‐IOP were significantly lower than of TVP‐IOP when IOP was higher than 14 mm Hg of TVP‐IOP. The characteristics of rebound tonometers should be considered in clinical settings.